Throughput analysis of non-orthogonal multiple access and orthogonal multiple access assisted wireless energy harvesting K-hop relaying networks - Phung Ton That; Nhat-Tien Nguyen; Duy-Hung Ha; Miroslav Voznak (International Journal of Electrical and Computer Engineering (IJECE), 2023)
This study introduces the non-orthogonal multiple access (NOMA) technique into the wireless energy harvesting K-hop relay network to increase throughput. The relays have no dedicated energy source and thus depend on energy harvested by wireless from a power beacon (PB). Recently, NOMA has been promoted as a technology with the potential to enhance connectivity, reduce latency, increase fairness amongst users, and raise spectral effectiveness compared to orthogonal multiple access (OMA) technology. For performance considerations, we derive exact throughput expressions for NOMA and OMA-assisted multi-hop relaying and compare the performance between the two. The obtained results are validated via Monte Carlo simulations.